P04 A quality improvement initiative to improve influenza and pneumococcal vaccination rates in patients receiving biological DMARDS (bDMARDs) in the mid-west of Ireland. (20th April 2020) - Ng, Wan Lin; Anjum, Aqeel; Sebastian, Alwin; Devlin, Joe; Fraser, Alexander
Abstract: Background: bDMARDs have been the panacea for rheumatic diseases but their use may increase the risk of infection. Morbidity and mortality in patients with chronic disease can be prevented with influenza and pneumococcal (PCV) vaccinations. Methods: We implemented a multifaceted quality improvement (QI) approach at our infusion unit using the Plan-Do-Study-Act methodology. Interventions included training of rheumatology nurses, individual patient consultations and distribution of Arthritis UK booklet on vaccination. During the first cycle, patients on bDMARDs attending the rheumatology infusion unit between January to April 2018 were recruited. Initial data included patients' demographics, diagnosis, bDMARD, their influenza and PCV vaccination statuses with reasons for not having vaccination. The second cycle was carried out from January to April 2019. Results: 92 patients were recruited in the first cycle; mean age was 53.2 years with 63 (68.5%) females. The uptake of vaccination was 52 (56.5%) for influenza and 31 (33.7%) for PCV. More importantly, 39 (42.4%) patients did not receive either vaccination. Of the 18 (19.6%) patients aged ≥65 years, 5 (27.8%) received influenza vaccination alone and 8 (44.4%) received both. The most common diagnosis from our cohort was rheumatoid arthritis (37%), followed by spondylarthritis (13%), Behçet's disease (9.8%) and others (40.2%). 48 (52.2%) were on rituximab, 37 (40.2%) on infliximab, 6 (6.5%) were on tocilizumab and 1 (1.1%) was on abatacept. 40 (43.5%) who did not receive the influenza vaccination stated that they were either unaware (45%), uninterested (25%), afraid of SEs (12.5%), forgotten (5%), unaware it was recommended (5%). Of the 61 (66.3%) patients who did not receive the PCV, 44 (72.1%) were unaware of its availability, 6 (9.8%) were uninterested, 8 (13.2%) were fearful of side effects (SEs) and 3 (4.9%) were unaware it was recommended. Patients who did not have vaccination were interviewed again during second cycle after QI interventions. There was satisfactory improvement in the vaccination rate of influenza vaccination (71.7%) and PCV (56.5%). The most common reason for the lack of vaccination were fear of SEs for influenza vaccination and unaware of its availability for PCV. 6 (9.7%) had serious infections in the preceding year requiring hospital admission; 3 had chest infections, 1 had urinary tract infection, 1 had cellulitis and 1 had necrotising fasciitis. Conclusion: Although the baseline vaccination rate was suboptimal in our cohort, there was a significant improvement after the QI interventions. The lack of awareness is the main reason for failure to be vaccinated. There is a need of a more robust action plan involving both the rheumatology team and primary care physicians to ensure adequate vaccination in immunocompromised patients. In the next step, we also aim to implement these QI interventions to the immunocompromised patients attending outpatient clinics. Disclosures: W. Ng None. A. Anjum None. A. Sebastian None. J. Devlin None. A. Fraser None.